Single Machine Scheduling Problem with Multiple Preventive Maintenance Levels and Setup Times - Yang, Mengyue; Dong, Wenjie; Liu, Sifeng (2023 5th International Conference on Data-driven Optimization of Complex Systems (DOCS), 2023)
Periodic preventive maintenance is often performed in many production systems to avoid sudden machine failures. In this paper, we study the single-machine scheduling problem with multiple periodic preventive maintenance (PM) levels and sequence-dependent setup times, where multiple PM levels correspond to multiple periodic types. A mixed integer programming model is formulated to minimize the total weighted tardiness. To solve the problem, a hybrid artificial bee colony algorithm is proposed and six local search strategies are designed. Computational experiments are conducted on instances to verify the performance of the algorithm.